Stereo- and regioselective hydroboration of 1-exo-methylene pyranoses: discovery of aryltriazolylmethyl C-galactopyranosides as selective galectin-1 inhibitors - Dahlqvist, Alexander; Furevi, Axel; Warlin, Niklas; Leffler, Hakon; Nilsson, Ulf J. (Beilstein Journal of Organic Chemistry, 2019)
Galectins are carbohydrate recognition proteins that bind carbohydrates containing galactose and are involved in cell signaling and cellular interactions, involving them in several diseases. We present the synthesis of (aryltriazolyl)methyl galactopyranoside galectin inhibitors using a highly diastereoselective hydroboration of C1-exo-methylene pyranosides giving inhibitors with fourfold or better selectivity for galectin-1 over galectin-3, -4C (C-terminal CRD), -4N (N-terminal CRD), -7, -8C, -8N, -9C, and -9N and dissociation constants down to 170 µM.
Keywords: C-galactoside; galectin-1; hydroboration; inhibition; selective; triazole